Teacher Performance Improvement In Building Quality Education - Tabroni, Imam; Maryani, Ade Heni; Sari, Rini Purnama (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Teachers play a very important role in carrying out their functions and duties as educators in realizing national education, because teachers are educators who will produce quality and quality students by providing knowledge to their students. To help the teacher's role in meeting these expectations, it is necessary to have efforts that can be taken to improve teacher performance in order to achieve quality education and produce quality students. Which educator or teacher will provide a direction in accordance with the guidelines which will produce results from the learning process that the nation and state can be proud of. This study aims to analyze improving the quality of education related to improving teacher performance. The quality of teachers can be improved through training programs and professional development as professional teachers